Curbing Petrochemical Lubricants by Plant-Based Chemicals: A Reliable Opportunity to Align with Sustainable Development Goals - Jaime Nácher-Mestre; David Leal Cano; Kudama A. Habib; Clemente M. Branchadell; Jaume Pérez-Sánchez (Lubricants)
The use of plant-based lubricants is a sustainable alternative to petrochemical lubricants. Their main advantages include proven tribological performance, higher biodegradability in the environment, and the absence of health hazards when inhaled, ingested, or in contact with the skin. In this study, nine best-selling commercial lubricants were purchased and compared with two proposed sustainable alternatives derived from plant-based resources. The alternative wet lubricant that was developed demonstrated superior tribological performance compared to the selected commercial lubricants. Meanwhile, the alternative dry lubricant exhibited a greater load capacity and high wear resistance in the presence of micrometric Al2O3 particles at 20 N. The results indicated that a proper formulation of plant-based resources in lubricants can achieve the same or even better functional performance than conventional lubricants, which are currently classified as hazardous under European regulations.